(untitled) (The Pakistan Development Review, 1999)
This paper addresses three complementary themes in bringing about responsive and accountable public governance in developing countries—namely globalisation, localisation and a results oriented management and evaluation (ROME). The first theme recognises interdependencies in an interconnected world and discusses how these influences would shape partnership within and across nations. The second theme is concerned with public sector realignments within nations to meet the challenges associated with heightened expectations from an informed citizenry. The third theme relates to creating a new culture of public governance that is responsive and accountable to citizens. The paper argues that a road to ROME holds significant promise of overcoming the ills of a dysfunctional, command and control, overbearing and rent seeking public sector in many developing countries. ROME de-emphasises traditional input controls and instead is concerned with creating an authorising environment in which the public officials are given the flexibility to manage for results but are held accountable for delivering public services consistent with citizen preferences. Further under ROME incentive mechanisms induce public and non-public (private and nongovernment) sectors to compete in the delivery of public services and match public services with citizen preferences at lower tax cost to society per unit of output.